2006
DOI: 10.1111/j.1600-051x.2006.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Nine‐ to fourteen‐year follow‐up of implant treatment. Part II: presence of peri‐implant lesions

Abstract: After 10 years in use without systematic supportive treatment, peri-implant lesions is a common clinical entity adjacent to titanium implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
544
8
14

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(612 citation statements)
references
References 26 publications
35
544
8
14
Order By: Relevance
“…An analysis of 987 implants followed for 9–14 years demonstrates that signs of mucositis (BoP) are evenly distributed among implants with or without peri‐implantitis. There was actually no difference in the proportion of implants with the absence or presence of bleeding/suppuration in relation to bone loss, bone gain, or bone stability (Roos‐Jansaker, Lindahl, Renvert & Renvert, 2006). Another large cohort study, including 4,591 implants from 2,060 subjects, indicated that minimal bleeding did not correlate with bone loss but multipoint bleeding, profuse bleeding, or suppuration did (French, Cochran & Ofec, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of 987 implants followed for 9–14 years demonstrates that signs of mucositis (BoP) are evenly distributed among implants with or without peri‐implantitis. There was actually no difference in the proportion of implants with the absence or presence of bleeding/suppuration in relation to bone loss, bone gain, or bone stability (Roos‐Jansaker, Lindahl, Renvert & Renvert, 2006). Another large cohort study, including 4,591 implants from 2,060 subjects, indicated that minimal bleeding did not correlate with bone loss but multipoint bleeding, profuse bleeding, or suppuration did (French, Cochran & Ofec, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of peri-implant mucositis has been reported to be in the range of 60% of implant recipients and in 48% of implants (Renvert et al, 2007;Roos-Jansaker et al, 2006a). The prevalence of peri-implantitis was found to be around 15, 16 and 28% with respect to the recipients (Fransson et al, 2005;Renvert et al, 2007;Roos-Jansaker et al, 2006a), and 7 and 12% regarding implant sites (Fransson et al, 2005;Roos-Jansaker et al, 2006a). The differences in the prevalence of peri-implantitis may be explained by differing criteria used for the diagnosis of peri-implantitis, as well as variations in maintenance procedures (Fransson et al, 2008;Zitzmann & Berglundh, 2008).…”
Section: Effects Of Chemical Cleaning Agents On Titanium Implant Surfmentioning
confidence: 99%
“…13 It has been shown that without systemic support, peri-implantitis is common. 35 Although Ruskin believes implants are superior to endodontically treated teeth due to their ability to resist dental caries, periodontal disease and structural deficiencies, implants with peri-implantitis do not seem to be very successful at resisting complications. 11 The treatment protocol for an implant that has peri-implantitis is to obtain a subgingival bacterial culture and then do a microbiological analysis of the culture.…”
Section: Inmentioning
confidence: 99%